Meningkatkan Kualitas Pembelajaran Melalui Implementasi Strategi Kontekstual - Faizah Fitrah; Sulthoni Alfathon; Gusmaneli Gusmaneli (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Education is a means of obtaining quality human resources to ensure the sustainability and progress of a nation. Education greatly influences the quality of a nation's human resources. Therefore, education must be promoted for all the young men and women of the nation's hopes. In achieving educational goals that make the life of the nation and state more intelligent, many things and methods are used for efficiency in the implementation of an educational process. One of them is the CTL (Contextual Teaching and Learning) learning approach method.